Pine needles attenuate receptor activator for nuclear factor-B ligand (RANKL)-induced trabecular bone loss by inhibiting osteoclast differentiation - Ki-Shuk Shim; Jin Yeul Ma (Integrative Medicine Research, 2018)
Background: The leaf of Pinus densiflora known as pine needles has been used to treat vascular disease, gastrointestinal diseases, and urinary diseases in traditional medicine. We evaluated anti-osteoporotic effect of water extract of Pinus densiflora (WEPN) on acute bone loss and osteoclastogenesis induced by receptor activator for nuclear factor-κB ligand (RANKL). Methods: After oral administration of WEPN (0.25 g/kg) for 5 days, femora were collected, and bone parameter [trabecular bone volume/tissue volume (BV/TV), trabecular thickness (Tb. Th), trabecular separation (Tb. Sp), trabecular number (Tb. N), and bone mineral density (BMD)] were analyzed by micro-CT analysis. Anti-osteoclastic effect of WEPN was examined using tartrate-resistant acid phosphatase activity and activation of RANKL signaling pathway. Results: We found that WEPN significantly attenuated RANKL-induced decrease of BV/TV, Tb.Th., Tb.N, and BMD but increase of Tb. Sp in femora. WEPN dose-dependently decreased osteoclastogenesis accompanied by inhibiting the activation of RANKL signaling components (JNK, p38, and p65) and mRNA expression level of osteoclast specific genes (NFATc1, c-Fos, TRAP, cathepsin K, DC-STAMP, and carbonic anhydrate). Conclusion: WEPN inhibition on osteoclastogenesis could contribute to attenuate RANKL-induced trabecular bone loss in vivo. Therefore, it might suggest that WEPN could be prescribed in traditional medicine or used in health functional food to prevent or treat osteoporotic bone diseases. Keywords: Pinus densiflora, Osteoclast, Receptor activator for nuclear factor-κB ligand, Nuclear factor of activated T cells cytoplasmic 1